Close encounters of the burned kind: Spatiotemporal effects of fire on habitat selection strategies of woodland caribou (Rangifer tarandus caribou) during winter - Russell, Kelsey L.M. (Author); Johnson, Chris (Thesis advisor); University of Northern British Columbia (Degree granting institution); Parker, Katherine (Committee member); Hegel, Troy (Committee member) (University of Northern British Columbia, 2018)
Forest fire is the primary natural disturbance process influencing the distribution and abundance of terrestrial lichens across ranges of woodland caribou (Rangifer tarandus caribou), including the Klaza Caribou Herd in west-central Yukon. I used stand and understory data to understand variation in the abundance of lichens in burns of various ages. Focusing on the distribution of individual caribou, I used a dataset of GPS collar locations to examine resource selection on the winter range and within burns. Results suggested that burns provided suboptimal habitat for the KCH until 50 years post-fire; however, analyses focused on the use of burned habitat indicated that they regularly encountered burns and opportunistically used remnant lichen within the burn perimeter. The relationship between caribou and burned landscapes is complex and non-linear indicating that wildlife managers should look beyond burn age to account for the effects of fire on the availability and quality of caribou habitat. woodland caribou rangifer tarandus caribou spatiotemporal habitat burn